The paying guests [large type] - Waters, Sarah, 1966- (Wheeler Publishing, 2015)
It is 1922, and London is tense. Ex-servicemen, the out-of-work and hungry are demanding change. In a genteel Camberwell villa -- a large, silent house now bereft of brothers, husband, and servants -- impoverished widow Mrs. Wray and her spinster daughter, Frances, are obliged to take in lodgers. Little do the Wrays know just how profoundly their new tenants will alter the course of Frances's life -- or how far-reaching the disturbances will be.